Perancangan Aplikasi E-Ticketing Pada Agen Bus Berbasis Website Menggunakan Laravel - Muhammad Haidar Wijaya; Magdalena A. Ineke Pakereng (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
Bus is the transportation which is still the main choice for the community which is easilyreached, by buying a ticket through a bus agent the community can enjoy the bus. However, inthe transaction process the customer must visit a bus agent to make a ticket purchase transaction.This is of course very impractical and the tickets that have been purchased are also vulnerable todamage and prone to loss. Therefore, an e-ticketing system is needed to support a more efficienttransaction process and minimize damage and loss of tickets. The laravel framework is used inmaking websites because the laravel framework provides a mail gateway system that makesticketing services easier to customers. The result of designing this application is an e-ticketingwebsite that can help the public in buying bus tickets and minimize damage and loss to tickets.